The 3D Printing in Material Research and Medical Physics Education and Its Accuracy Study - Talitha Asmaria; Rafida Rahmi; Muhammad Satrio Utomo; Franciska Pramuji Lestari; Aprillia Erryani; Patmah Fathoni; Tutun Nugraha; Ika Kartika (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
This study aims to construct prototypes using three-dimensional (3D) printing technology as a research apparatus and a physics education instrument, particularly in medical physics education. Two main designs of prototypes have been arranged. Two foam NaCl templates are drawn using computer-aided design (CAD) software. Image processing techniques achieve a 3D model of a thoracic vertebra. All 3D model data are printed using polylactic acid (PLA) filament. The prints of foam NaCl templates are utilized for holding the NaCl powder. The prototype of a human vertebra is used for visualization of the real condition of the human bone anatomy. The results of the prototypes are analyzed to investigate the similarity between the model and the prints. This investigation is done using a Vernier Caliper and CT Scan. The measurement using Caliper shows a higher percentage in likeness than the CT-Scan. All the accuracy study shows they have more than 83% in similarity. It can be concluded that all built prototypes have prominent exactitude and can support the material research using the printed NaCl templates. Hereafter, a bone mock-up’s genuine perception can function for further application, such as implant or surgery planning.